A correlação entre mídia, opinião pública e os julgamentos em matéria penal - Araujo, Ricardo Manoel Cruz de (2019)
The present work aims to approach the media, public opinion, the criminal process and the Judiciary, analyzing the correlation between them. The analysis is made on the basis of doctrine and examples of real cases. The media, in its various aspects, and the manifestation of the population, which is often verbal, use the mass media to give an opinion about the progress of the processes involving crimes. This external interference can undermine the good service provided by the Judiciary, causing serious consequences, removing from the criminal law one of its main characteristics, which is trying to reach as close as possible to the real truth, where one seeks a true reality of facts, trying to be as reliable as possible to what happened in the real case, thus distancing itself from speculation. Failure to pursue the truth of facts in criminal legal proceedings can lead to injustice and consequently entails an injury, which often affects the dignity of the human person. It is necessary to analyze the principles that must govern the Criminal Procedure, as well as the constitutional principles in which they should be validated, once the Judge should not simply rely on public opinion or media ,he or she has the duty to respect the principle of impartiality and the verdict must be based on the knowledge he or she has on the case. To do so, one must use all possible means and therefore escape from misunderstood interpretation.